Person, place, and pragmatism: Theorizing urban spaces - Aaron Martin; Amal Shukr (Cogent Business & Management, 2024)
Cities old and new would benefit if they embraced a perspective distinct from the dominant thought regarding efforts to reinvent or contemporize themselves through urban renewal projects, specifically those related to social inclusion. Realism, as contrary to pragmatism, has been shown to impose a complacent attitude toward vulnerable urban communities through its attachments to predeterminacy. This paper analyzes the detrimental effects of a realist worldview on marginalized populations facing displacement as a result of these projects, and takes a Rortyan approach at delineating the implications of realist policy approaches in cities like Los Angeles, California, Detroit, Michigan, and Birmingham, England. The paper then turns to critique movements like `Detroit vs Everybody' and Richard Florida's model in The Rise of the Creative Class as an effort to endorse a reconceptualization of policies in which elites relinquish their realist attachments in favor of outcome driven, pragmatic solutions that will, in turn, relieve these marginalized groups of the infringement imposed upon them.
Keywords: 650; urban renewal; pragmatism; Richard Rorty; realism; creative class; third place; city planning